PREVALENCE OF DEPRESSION IN COMMON POPULATION:A COMMUNITY BASED STUDY - Dona Johnson, Dona Johnson; Aneeta Jacob, Aneeta Jacob; Anvy Thankachan, Anvy Thankachan; Jeena Jacob, Jeena Jacob; Joyal Anna Babu, Joyal Anna Babu (International Journal of Indigenous Herbs and Drugs, 2020)
Depression is a common cause of disability and reduced life satisfaction and also the most prevalent mental disorder. This is a community-based study in the common population. A total of 150 people were recruited in this study. The study population includes males and females, married and unmarried, students, farmers, govt. employees, IT professionals as well as health professionals randomly. The questionnaire is based on the Montgomery and Asberg Depression Rating Scale (MADR Scale). The result of the study shows the existence of depressive symptoms in the community. Based on the score obtained, the symptoms were classified as mild, moderate, and severe. About 23.3% of people affected with chronic depressive symptoms.  Females affected with severe depressive symptoms (30 females) than in males (15 males). In the case of different age groups younger adults (35 people) shows more severe symptoms than elder adults (15 people).